La Verneda-Sant Martí Adult Education Center: Dialogic Learning and Democratic Participation both Within and Without - Marta Soler; Adriana Aubert (Adult Education Research Conference, 2001)
This case study describes Multi-user domains (MUDS) as a virtual learning environment for fostering the imaginative and symbolic aspects of transformative learning by relying primarily on the work of Boyd and Freire. MUDs are an increasingly popular but largely unexplored location for adult learning.